NKp46+ natural killer cells develop an activated/memory-like phenotype and contribute to innate immunity against experimental filarial infection - Pionnier, Nicolas; Furlong-Silva, Julio; Colombo, Stefano A. P.; Marriott, Amy E.; Chunda, Valerine C.; Ndzeshang, Bertrand L.; Sjoberg, Hanna; Archer, John; Steven, Andrew; Wanji, Samuel; Taylor, Mark J.; Turner, Joseph D. (Frontiers in Immunology, 2022)
Lymphatic filariasis and onchocerciasis are major neglected tropical diseases affecting over 90 million people worldwide with painful and profoundly disfiguring pathologies (such as lymphoedema or blindness). Type 2 inflammation is a hallmark of filarial nematode tissue infection and is implicated both in eosinophil dependent immunity and lymphatic or ocular immunopathologies. Type-2 innate lymphoid cells (ILC2) are known to play an important role in the initiation of type 2 inflammation in helminth infection. We therefore tracked comparative IL-12Rβ2+ ILC1, ST2+ ILC2 and NKp46+ natural killer (NK) innate lymphoid cell population expansions during Brugia malayi experimental peritoneal filarial infections using either immunocompetent or immunodeficient mice. In immunocompetent BALB/c animals, NKp46+ NK cells rapidly expanded representing over 90% of the ILC population in the first week of infection, whereas, surprisingly, ST2+ ILC2 failed to expand. NKp46+ NK cell expansions were confirmed in RAG2 deficient mice lacking adaptive immunity. Ablation of the NKp46+ NK cell compartment in RAG2 common gamma chain (gc) mice led to increased susceptibility to chronic adult B. malayi infection. This data was recapitulated using an Onchocerca ochengi male worm peritoneal implant model. When NKp46+ NK cells were depleted in RAG2 deficient mice using anti-NKp46 or asialo GM1 antibody injections over the first five weeks of B. malayi infection, susceptibility to adult B. malayi infection was significantly increased by 2-3 fold with concomitant impairment in eosinophil or neutrophil recruitments. Finally, we demonstrate that in RAG2 deficient mice, drug clearance of a primary adult B. malayi infection followed by challenge infection leads to resistance against early larval B. malayi establishment. This innate resistance is associated with bolstered NK and eosinophils whereby NKp46+ NK cells express markers of memory-like/enhanced activation (increased expression of interferon gamma and Ly6C). Our data promotes a novel functional role for NKp46+ NK cells in immunoprotection against experimental primary and secondary filarial infection which can proceed in the absence of adaptive immune regulation.